Evaluation of Serum Creatinine in Hypertensive Patient - Yadav, Shekhar Chandra (Journal of Nobel Medical College, 2016)
Background The study is carried out to evaluate serum creatinine in hypertensive patients in Nobel Medical College Teaching Hospital, Biratnagar, Nepal.Material and Methods The study was carried out on total 100 subjects, with a) Case groups (Hypertensive Subjects), n= 50 b) Control groups (Non-Hypertensive Subjects), n=50 with no present and past family history of hypertension, in the Department of Biochemistry, Nobel Medical College Teaching Hospital, Biratnagar, Nepal from 21st March 2013 to 30th july2014, after Institutional Ethical Approval. venous blood sample was collected and sample was analysed for serum creatinine level by Jaffe’s method.Result serum creatinine is significantly increased in case group with the Mean of 1.17±0.25 when compared to control group Mean of 1.05±0.14 with p= 0.002. Thus, showing a suggestive significant of serum creatinine levels in cases when compared to control group.Conclusion The hypertensive patients have significant alteration in serum creatinine level and are likely to developed chronic kidney disease. Thus, it is indicated to have serum creatinine estimation in daily clinical practice. Journal of Nobel Medical College Vol.5(2) 2016; 56-59